2012
DOI: 10.14490/jjss.42.145
|View full text |Cite
|
Sign up to set email alerts
|

Profile Analysis with Random-Effects Covariance Structure

Abstract: In this paper, we consider a parallel profile model for several groups. Given the parallel profile model we construct tests based on the likelihood ratio, without any restrictions on the parameter space, for testing the covariance matrix for random-effects structure or sphericity. Furthermore, given both the parallel profile and random-effects covariance structure the level hypothesis is tested. The attained significance levels and the empirical powers for the given tests in this paper are compared with the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Remark 1. As we mentioned in Section 1, Srivastava and Singull (2012) suggest using the M-LRT even in the case of testing (1.4) although the M-LRT is derived for testing (1.5). However, the null hypothesis H 0 * considered by Srivastava and Singull (2012) includes H 11 (i.e., H 11 is a part of the null hypothesis H 0 * ).…”
Section: Conservativeness and Powermentioning
confidence: 99%
See 2 more Smart Citations
“…Remark 1. As we mentioned in Section 1, Srivastava and Singull (2012) suggest using the M-LRT even in the case of testing (1.4) although the M-LRT is derived for testing (1.5). However, the null hypothesis H 0 * considered by Srivastava and Singull (2012) includes H 11 (i.e., H 11 is a part of the null hypothesis H 0 * ).…”
Section: Conservativeness and Powermentioning
confidence: 99%
“…Then, the hypothesis (1.5) is tested by using χ 2 f . Under H 0 Srivastava and Singull (2012) showed that the limiting approximation of the distribution of the M-LRT is better than that of the R-LRT proposed by Yokoyama (1995). Moreover, through numerical experiments, they also showed that the power for the M-LRT is larger than the power for the R-LRT.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This class of model has been considered by many authors and estimation of parameters of interest has been discussed with different choices of C and Z. See for example Nummi (1997); Ip et al (2007); Lange and Laird (1989); Yokoyama and Fujikoshi (1993); Yokoyama (2001); Srivastava and Singull (2012) for more details.…”
Section: Random Effect Growth Curve Modelmentioning
confidence: 99%
“…This class of models has been considered by many authors and estimation of parameters of interest has been discussed with different choices of A and Z. See for example Nummi (1997); Ip et al (2007); Lange and Laird (1989); Yokoyama and Fujikoshi (1993);Yokoyama (2001); Srivastava and Singull (2012) for more details. In what follows, we consider a particular case where Σ e has simple structure, i.e., Σ e = σ 2 e I p and present the estimation and prediction framework in model (2.11).…”
Section: Random Effects Growth Curve Modelsmentioning
confidence: 99%